Reversal of left ventricular dysfunction after ablation of premature ventricular contractions related parameters, paradoxes and exceptions to the rule. (1st November 2016) - Sadron Blaye-Felice, Marie; Hamon, David; Sacher, Frederic; Pasquale, Patrizio; Rollin, Anne; Bongard, Vanina; Duparc, Alexandre; Mondoly, Pierre; Derval, Nicolas; Denis, Arnaud; Cardin, Christelle; Hocini, Mélèze; et al.
Abstract: Background: Suppression of frequent premature ventricular contractions (PVCs) does not systematically lead to an expected reversal of PVC-induced cardiomyopathy and determinants of left ventricular ejection fraction (LVEF) recovery (reverse remodeling) after ablation remain largely unknown. Methods: Ninety-six consecutive patients with a suspicion of PVC induced-cardiomyopathy were retrospectively included. Parameters potentially related to reverse remodeling (> 10% increase in LVEF) were analyzed in patients w/wo long-term success (decrease in PVC burden > 80%). Results: Over a mean follow-up of 24 ± 21 months, long-term ablation success was obtained in 76 patients (79%). In these, reverse remodeling was observed in 63 (83%) (LVEF 39 ± 8 to 56 ± 8%, p < 0.0001). In multivariate analysis, only an older age (and marginally a lower PVC QRS amplitude) was independently associated with the lack of reverse remodeling. Only 10 of the 35 patients who initially should have received an ICD for primary prevention remained candidates for implantation after ablation. Lack of reverse remodeling was significantly linked to a higher mortality. Conclusion: Reverse remodeling was observed in 83% of patients with frequent PVC and unexplained cardiomyopathy undergoing long-term successful ablation of the PVC. A younger age was independently correlated with the occurrence of reverse remodeling.